SIFAT FISIK DAN MEKANIK PAPAN SERAT BATANG PISANG KEPOK (Musa paradisiaca. L) PADA BERBAGAI SUHU DAN WAKTU KEMPA - Maftuhatin, Via Mahardika; Indrayani, Yuliati; Yani, Ahmad (JURNAL HUTAN LESTARI, 2017)
This research aims to identify the optimal pressing temperatures and time of a fibre board made from kepok banana stem. The target of density for this fibre board is 0.6 gr/cm3). The board was made by dividing the fibre into three different parts with the same weight (weight ration 1:1:1). After that, each fibre was applied adhesive mixtures by a means of spraying the mixture evenly with a hand sprayer. Having evenly mixed, the fibre was put into a 30 cm Ã— 30 cm Ã— 1 cm mold by an intersecting perpendicular. The physical and mechanical properties were examined based on JIS (Japanese Industrial Standard) A 5906-2003. In this research, the variables of observation involved physical properties (density, water content, thickness swelling, and water absorption) and mechanical properties (MOE, MOR, bonding strength, grasp screw strength). The results revealed that the averagevalue of physical properties were stated as follows: the board density was between 0.5618-0.6268 gr/cm3, the water content was between 9.1438%-10.2041 %, the water absorption was between 148.5961% - 120.5571%, the thickness swelling was between 15.5167%-23.9611%. Meanwhile, the average value of mechanical properties were recorded as follows: MOE was between 10553.3831 kg/cm2-15199.4095 kg/cm2, MOR was between 208.2067 kg/cm2-270.0940 kg/cm2, bonding strength was between 0.5012 kg/cm2-1.0790 kg/cm2, grasp screw strength was between 30.9408 kg - 43.3176 kg. The fibre board with temperature 1800C and 10 minutes of prssing time constituted as the optimal treatment to produce a fibre board which met the standard of JIS A 5905-2003 type 5,15,25, and 30.Keywords: fibre board, kepok banana fibre, pressing temperature, pressing time.